2015
DOI: 10.5858/arpa.2014-0028-oa
|View full text |Cite
|
Sign up to set email alerts
|

Prior High-Risk Human Papillomavirus Testing and Papanicolaou Test Results of 70 Invasive Cervical Carcinomas Diagnosed in 2012: Results of a Retrospective Multicenter Study

Abstract: Context.-Persistent high-risk human papillomavirus (hrHPV) infection is essential for the development of cervical cancer and its precursor lesions. High-risk HPV testing has a higher sensitivity than cytology does for detecting cervical epithelial lesions. However, a large study from a single institution showed 31% of patients with invasive cervical cancer had negative baseline hrHPV testing within 5 years preceding the diagnosis.Objective.-To investigate the limitation of hrHPV testing in detecting invasive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 20 publications
4
40
0
5
Order By: Relevance
“…Similarly, Zhao et al 23 reported that 9%-25% of patients with squamous cell carcinoma (SCC) had negative hrHPV test results in the preceding 1-5 years. The data from the Kaiser Permanente study showed that 37% of women with SCC were HPV-negative 5 years before the histological diagnosis of cervical cancer.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, Zhao et al 23 reported that 9%-25% of patients with squamous cell carcinoma (SCC) had negative hrHPV test results in the preceding 1-5 years. The data from the Kaiser Permanente study showed that 37% of women with SCC were HPV-negative 5 years before the histological diagnosis of cervical cancer.…”
Section: Discussionmentioning
confidence: 97%
“…Diğer ülkelerde yapılan çalışmalara bakıldığında ise, HPV6, HPV11 ve HPV31 en sık izlenen tiplerdir (16). Smear preparatlarının Papanikolaou smear ile incelenmesi, servikal kanser insidansını azaltmada başarılı bir yöntem olmakla birlikte; HPV saptanmasının daha sensitif olduğunu ileri süren çalışmalar da mevcuttur (19). Zhao ve ark.…”
Section: Discussionunclassified
“…Zhao ve ark. (19), invaziv servikal kanserli olgularının %31'inin HPV negatif olduğunu belirtmişlerdir. Literatürde buna benzer sonuçlar bulan başka çalışmalar da vardır (20,21).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Some studies have demonstrated that 10% of cervical tissues in US tumor registries do not contain detectible HPV 25 and that 37% of cervical adenocarcinomas around the world are HPV negative. 26 Similarly, studies following up patients for an extended time have shown higher rates of baseline negative HPV results in patients with cervical cancer, 27 a point that questions both the prevalence of HPV positivity in cervical cancers and the length of follow-up time in these studies used to support the interim guidance. If a significant percentage of cervical cancers are not causally related to an HPV infection or do not test HPV positive with current methods, a screening algorithm that keeps HPV-negative women in a general screening pool could miss clinically significant lesions.…”
Section: Interim Guidancementioning
confidence: 99%